ANALYSIS OF THE ELEMENTS OF THE PRODUCTION COSTS - Daniela SIMTION (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Classical methods for calculating costs underlay the organization activity of measuring costs and have maintained due to the existence of basically the same technical, technological and organizational production structures. Of course, technical progress has brought a number of changes in the productive structure, this is the reason due to which the classical methods of calculation have evolved while preserving their essence and becoming basic methods of cost management. This paper present a study case regarding analysis of the items of production costs in order to set the strategy of the company for reducing production cost.